Characterization of Five Purine Riboswitches in Cellular and Cell-Free Expression Systems - Lins, Milca Rachel da Costa Ribeiro [UNESP]; Corrêa, Graciely Gomes [UNESP]; Amorim, Laura Araujo da Silva [UNESP]; Franco, Rafael Augusto Lopes [UNESP]; Ribeiro, Nathan Vinicius [UNESP]; Jesus, Victor Nunes de [UNESP]; Pedrolli, Danielle Biscaro [UNESP] (Springer Nature, 2022)
Bacillus subtilis employs five purine riboswitches for the control of purine de novo synthesis and transport at the transcription level. All of them are formed by a structurally conserved aptamer, and a variable expression platform harboring a rho-independent transcription terminator. In this study, we characterized all five purine riboswitches under the context of active gene expression processes both in vitro and in vivo. We identified transcription pause sites located in the expression platform upstream of the terminator of each riboswitch. Moreover, we defined a correlation between in vitro transcription readthrough and in vivo gene expression. Our in vitro assay demonstrated that the riboswitches operate in the micromolar range of concentration for the cognate metabolite. Our in vivo assay showed the dynamics of the control of gene expression by each riboswitch. This study deepens the knowledge of the regulatory mechanism of purine riboswitches.